Huat Ah! Huat Ah! - Tan, Boon Huat; Annu; Joyce, Cheng (Petaling Jaya : Red Films Sdn. Bhd, 2014)
HUAT AH! HUAT AH! HUAT is an inspirational comedy for audiences of all ages. The film tells the story of Ah Huat, a youth who strives for success but never goes against his motto of 2being honest3. Ah Huat reflects the typical Malaysian Chinese who treats everyone with kindness and sincerity.
Cinematography by Haris Sue ; film editing by Aliastair Tham Mun, Hoe.
Annu, Joyce Cheng.
DVD format, MPEG, PAL, Surround 5.1, Region 3.
In Mandarin with optional English, Chinese and Malay subtitles.
Title from title screen.
Keywords: Comedy films